Return to work after breast reduction - Holopainen, Nora (My University, 2022)
Introduction Breast hypertrophy is a prevalent condition among women worldwide, which can affect different aspects of their quality of life. Uncertainty exists in the medical literature about recommendations for return to work after reduction mammaplasty procedures. The aim of this study was to assess the return to work after reduction mammaplasty for women with breast hypertrophy. Material and Methods A retrospective cohort study composed of chart review of all reduction mammaplasty performed at a single institution due to breast hypertrophy was considered. Patients not in working life were excluded. Patients were divided into two groups on the basis of the sick leave duration: normal versus prolonged. Prolonged sick leave time was defined as times greater than the 75th percentile for the respective sample data. Demographic and comorbidity data were secondary predictor variables. The primary outcome measure was the occurrence of prolonged sick leave. Secondary endpoints were specific wound healing complications and late complications. We further compare postoperative complications between patients who received a sick leave of 3 weeks versus the other patients’ cohort. Results From a total of 490 patients, 407 of them were employed at intake. Mean time to working return after reduction mammaplasty was 4.0±0.9 weeks. Prolonged sick leave occurred in 77 patients and its mean duration was 5.5±0.9 weeks. No differences in age, preoperative BMI, smoking, comorbidities, number of children or use of herbal supplements were detected. Increased intraoperative blood loss appeared in the group who received prolonged sick leave (328.3 ml vs 279.2 ml , p=0.031). Otherwise, no differences in perioperative parameters. Postoperative complications were significantly higher in the group who experienced a prolonged sick leave (26.5% vs 11.2%, p<0.001), particularly infections and wound dehiscence incidences were higher. However, no differences in late complications (>30 days, 6.5% vs 7.6%, p=0.729). When comparing patients who received a 3-week sick leave with the rest of cohort, blood loss was significantly higher in the group who experienced a sick leave longer than 3 weeks (230.9 ml vs 303.7 ml, p <0.001). Conclusion The occurrence of postoperative complications increased the patients’ return to work time. Comorbidities and preoperative parameters did not affect the length of sick leave. It appears reasonable to suggest a recovery period of approximately 3 weeks subject to individual variations. An increased intraoperative blood loss might predict a prolonged sick leave.